2004
DOI: 10.1016/j.ejcts.2004.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Aortoventriculoplasty and left ventricle function: long-term follow-up

Abstract: Improvement of the systolic function after the surgery was noted in both groups. In patients with low AOVI%, postsurgical pressure gradient, either residual or recurrent, appeared during the follow-up. As for the septal incision, it may have some transient effects on the left ventricle function in the postoperative period, but no permanent sequelae were observed in the long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similar combinations of complex left-sided obstruction treated by the Konno procedure have been reported elsewhere. 19,21,24,32 The range and frequency of most perioperative nonfatal complications, including an 11% incidence of permanent heart block, parallel the results of others. 17,19,28 Operative mortality in our study was 8% and long-term survival at 10 years was 86%, again comparable to results reported elsewhere.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar combinations of complex left-sided obstruction treated by the Konno procedure have been reported elsewhere. 19,21,24,32 The range and frequency of most perioperative nonfatal complications, including an 11% incidence of permanent heart block, parallel the results of others. 17,19,28 Operative mortality in our study was 8% and long-term survival at 10 years was 86%, again comparable to results reported elsewhere.…”
Section: Discussionmentioning
confidence: 69%
“…Echocardiographic follow-up demonstrated that after an initial postoperative decline, ejection fraction stabilized with time after the Konno procedure. Although it was initially suggested in the literature that biventricular incisions might adversely impact postoperative cardiac function, a recent report by Sharma and associates 32 demonstrated that the recovery of ventricular function after the Konno procedure is analogous to that seen after aortic valve replacement alone. We are cognizant of the fact that the values observed at the last follow-up were probably affected by the small numbers of patients available for study.…”
Section: Discussionmentioning
confidence: 99%
“…3 Placement of mechanical valves in small children often requires extensive annular enlargement to accommodate an adequate prosthesis; this enlargement may be more extensive than that required for an autograft or homograft and may result in late left ventricular dysfunction. 23 In light of the imperfect choices for valve replacement in children, it would seem desirable to avoid valve replacement at the expense of acceptable residual lesions.…”
Section: Discussionmentioning
confidence: 99%